Mechanical properties of polyamide 11 and thermoplastic polyurethane polymers fabricated by multi jet fusion - Lim, Sean (Nanyang Technological University, 2020)
Additive manufacturing is a process whereby parts are produced layer wise. One of the processes in additive manufacturing the multi jet fusion (MJF) technique from HP, which became available commercially in 2016. In this technique, the material powder is thermally fused layer by layer via an infrared heat source. Polymer powders have been adopted in the MJF process, with polyamide 12 being one of the most used. Other polymers such as polyamide 11 (PA11) and thermoplastic polyurethane (TPU) are also feasible in this process, creating possibilities to manufacture parts with different properties. However, not much research has been published with these 2 polymer powders as the material in MJF. As such, this report seeks to systematically investigate the use of PA11 and TPU in the MJF process. In this project, MJF 3D printed PA11 and TPU samples underwent various tests to determine their properties. Tensile tests, flexural tests, thermal analyses and surface roughness were carried out to investigate the tensile, flexural, thermal and surface roughness properties of the samples. From the results, the research published in this report can then be used for future research involving these 2 polymer powders in MJF.